On the mass transfer performance enhancement of membraneless redox flow cells with mixing promoters. (March 2017) - Marschewski, Julian; Ruch, Patrick; Ebejer, Neil; Huerta Kanan, Omar; Lhermitte, Gaspard; Cabrol, Quentin; Michel, Bruno; Poulikakos, Dimos
Highlights: Membraneless microfluidic flow cell with herringbone-inspired flow promoters. Polarization curve analysis using dilute anthraquinone/iron redox system. Flow promoters substantially increase mass transfer. Limiting current: more than doubled at Re >155, steeper scaling regime of Re 0.58 . Abstract: Membraneless flow cells for electrochemical energy conversion exploit the laminarity of microscale flows to avoid undesirable mixing of reactants. To increase the performance of microfluidic redox flow cells we employ herringbone-inspired flow promoters, thereby increasing convection of each individual species to the electrodes, while minimizing reactant mixing. Polarization curves from electrochemical discharge measurements with a dilute anthraquinone/iron redox system reveal that the presence of flow promoters substantially boosts device performance. Mass transfer enhancement for devices with flow promoters is demonstrated through both higher limiting currents and increased power density; the former is more than double compared to a plain reference microchannel for Reynolds numbers of Re >155. The chaotic mixing effect induced by the flow promoters also becomes apparent in the scaling regimes, the limiting currents are proportional to Re 0.58 instead of Re 1/3 (as for purely laminar flow). Further, we quantify the area specific resistance (ASR) of the electrolyte in our membraneless devices finding a reduction of more than one order of magnitude compared to the ASR of conventional membranes employed in redox flow cells. Overcoming mass transfer limitations, this work highlights the necessity of passive mixers in significantly raising the performance of microfluidic flow cells.